Animal Husbandry Extension Service Delivery: Farmers’ Perception in Four Major Indian States - Kareem, MA; Phand, SS; Manohari, PL; Borade, M (Journal of Agricultural Extension Management, 2018)
The present study was conducted to analyze farmers’ perception on the effectiveness of animal husbandry extension services delivery in four major Indian states viz., Karnataka, Maharashtra, Odisha and Uttar Pradesh. Purposive sampling technique was used for the sample selection. A questionnaire was used to elicit information from 80 sample respondents. Data were analyzed using descriptive statistics such as mean, frequency counts, percentages, standard deviation and Kruskal-Wallis test. Results showed that majority of the farmers (48.75 per cent) belonged to middle age group with more than 20 years of experience (41.25 per cent) and majority (91.25 per cent) of the interviewed were full-time farmers in the small farmer (35 per cent) category with 1.1 to 2.0 ha land. With regards to extension contact, the cumulative frequency indicates that animal husbandry officer is the most contacted person as he/she is in touch with farmers in the service area. Thirty-nine practices scaled by 20 farmers from each state on a three-point continuum scale reveal that majority of the farmers were moderately satisfied with the services of animal husbandry officers, with farmers in Maharashtra state being more satisfied followed by Karnataka, Uttar Pradesh and Odisha. Based on the study findings it is concluded that for animal husbandry extension to be efficient, effective and visible, there needs to be more integration among the extension personnel of agriculture and allied sectors. The study recommends a review of extension methods perceived to be non-effective or slightly effective and collaboration among the stakeholders for strong extension services. It will be imperative to ensure that methods considered to be effective are mainly used to deliver extension messages.